Functional attributes of seminal proteins in bull fertility: a systematic review. Issue 4 (April 2021) - Viana, Arabela Guedes de Azevedo; Ribeiro, Iara Magalhães; Carvalho, Renner Philipe Rodrigues; Memili, Erdogan; Moura, Arlindo Alencar; Machado-Neves, Mariana
Abstract : Proteomic approaches have been widely used in reproductive studies to uncover protein biomarkers of bull fertility. Seminal plasma is one of the most relevant sources of these proteins that may influence sperm physiology. Nonetheless, there are still gaps in existing knowledge in the functional attributes of seminal proteins. Thus, we reviewed the relationships between seminal plasma proteins and bull fertility by conducting a systematic review with data obtained from 71 studies. This review showed that the associations related to fertility improvement with the use of total seminal plasma proteins are still controversial. None of the studies explored the sperm fertilizing ability following these interactions. By contrast, the exposure to a single protein, such as osteopontin, binder of sperm proteins, and heparin binding proteins, can increment sperm motility, capacitation, and fertilizing ability by modulating intracellular calcium concentrations, removing lipids from sperm membranes, and regulating the acrosome reaction. Variations in protein analyses and the protein contents and their abundances between animals contributed to the difficulty of establishing protein biomarkers of fertilizing potential of the bull sperm. Indeed, the heterogenicity of methodologies was a limitation of this review. Standardized methods of seminal protein analyses, as well as sperm endpoints, may minimize such discrepancies. In conclusion, potential biomarkers of sperm parameters are still to be established. Future studies should evaluate protein isoforms and how they interact with sperm to ascertain their biological functions.